If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 56 = 5x + 40 Reorder the terms: 56 + -3x = 5x + 40 Reorder the terms: 56 + -3x = 40 + 5x Solving 56 + -3x = 40 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 56 + -3x + -5x = 40 + 5x + -5x Combine like terms: -3x + -5x = -8x 56 + -8x = 40 + 5x + -5x Combine like terms: 5x + -5x = 0 56 + -8x = 40 + 0 56 + -8x = 40 Add '-56' to each side of the equation. 56 + -56 + -8x = 40 + -56 Combine like terms: 56 + -56 = 0 0 + -8x = 40 + -56 -8x = 40 + -56 Combine like terms: 40 + -56 = -16 -8x = -16 Divide each side by '-8'. x = 2 Simplifying x = 2
| 30+15x-3x=114 | | -3a-8=4 | | 69+x+(x-3)=180 | | 4X+6=10X-8 | | x^5=1/243 | | -38=-7x-2x-2 | | 6x+131=13x-9 | | F(x)=x^5+2x | | 0.01+x=0.09 | | 7(4w+8)=5 | | 18x+1(1)=4(x+1) | | 3(x-2)=2x+12 | | 28w=-51 | | http://www.mathsolution.ru/math-task/derivative | | 16(y^2-64x)-16(y^2-96y)=-199 | | (3x^2+26x+48)(2x-9)=0 | | x+x+1=240 | | (2x-9)(3x^2+26x+48)=0 | | 10-3b+14=2b-18+7b | | -2(2t+3)=6 | | Logx+log(x-1)=2 | | e^7x=9 | | 9/6=102 | | 16=-5+7b | | 3x(sqrt(x+12))+6(x+12)(sqrt(x+12))=0 | | 2(f-8)=-26 | | 11x-11=4x+10 | | 3b/2-4=2b/3-2/3 | | 62/24-5/4 | | 5*y= | | h/-27=102 | | 24=10x+32 |